Aktivitas Antikanker Nanokapsul Ekstrak Mengkudu (Morinda citrifolia L.) dengan Pengujian in Vivo pada Fibrosarkoma Mencit Jantan Balb/c - Nur Aisyah; Lulus Kartika Ningtias; Ancah Caesarina Novi Marchianti; Bambang Piluharto; Deltaningtyas Tri Cahyaningrum; Naning Retnowati; Nurud Diniyah; Iswahyono Iswahyono; Riska Rian Fauziah (JURNAL AGROTEKNOLOGI, 2022)
Noni (Morinda citrifolia L.) is one of the many herbs which known as an anticancer agent. Nanoencapsulated form of noni extracts could help the body absorption and able to inhibit the proliferation of cancer cells in vitro. This study was conducted to examine the anticancer activity of nanoencapsulated noni extracts in vivo as the anti-proliferation agent of cancer cells. Noni extract was obtained by maceration method using water as a solvent. The nanocapsule of noni extracts was made using the ionic gelation method by magnetic stirrer with the speed of 1500 rpm. In vivo anticancer activity test was conducted in Balb/c male mice by comparing the treatment of nanoencapsulation noni extracts and non-encapsulated extracts. The result showed that the nanoencapsulated noni extracts have a particle size of 27-59 nm. Percent of inhibition of nanocapsule on cancer cells (specifically on fibrosarcoma of Balb/c male mice) were equal to 54.75% (P2), while non-encapsulated is 49.72% (P1). Nanocapsule of noni extracts has anticancer activity better than non-encapsulated form on fibrosarcoma of Balb/c male mice. Keywords: anticancer, nanoencapsulation, noni extract